Effect of calcination temperature on sensing properties of Bi3NbTiO9. (April 2015) - Cheng, W. L.; Zhang, D. L.; Yan, D.; Li, B. R.
<x content-type="archive" xml:space="preserve">Abstract</x> With Bi2O3, TiO2 and Nb2O5 as the starting materials, the conventional solid-state reaction method was used to fabricate Bi3NbTiO9 powders. The mixture of Bi2O3, TiO2 and Nb2O5 was calcinated at different temperatures. After being characterised using X-ray diffraction, differential thermal analysis and scanning electron microscopy techniques, the as-prepared powders were used to fabricate humidity sensors for investigating the possible effects of crystal structure on the electric properties. The results indicated that the calcination temperatures had significant effects on the humidity properties of Bi3NbTiO9. In comparison with the 773 and 1073 K samples, the humidity hysteresis of the 573, 873 and 1173 K samples were smaller. Besides, among all the samples, the response and recovery time of the 773 K sample was found to be the best. Further studies revealed the discrepancy in humidity properties was attributed to the structural evolution with temperature increasing and Bi3NbTiO9 prepared by the conventional method can be used for high-performance humidity sensor by controlling the calcination process.